2019
DOI: 10.1016/j.jcf.2019.04.017
|View full text |Cite
|
Sign up to set email alerts
|

Use of inhaled imipenem/cilastatin in pediatric patients with cystic fibrosis: A case series

Abstract: Mycobacterium abscessus is a rapidly-growing, virulent, non-tuberculous mycobacterium that causes progressive inflammatory lung damage and significant decline in lung functionin patients with cystic fibrosis. M. abscessus complex pulmonary infections are notoriously difficult to treat, and while many antibiotics are approved for children, drug allergies or intolerances can prohibit their use. Intravenous imipenem/cilastatin is among the preferred antibiotics for treatment of M. abscessus, however, its use may … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Imipenem is one of the most reliable antibiotics used to treat M. abscessus infections. 17,18 Recently, however, imipenem-resistant M. abscessus has emerged; the underlying resistance mechanism remains to be delineated fully. The present study confirmed the high rate of M. abscessus resistance to imipenem based upon analysis of a large number of clinical isolates obtained in mainland China.…”
Section: Discussionmentioning
confidence: 99%
“…Imipenem is one of the most reliable antibiotics used to treat M. abscessus infections. 17,18 Recently, however, imipenem-resistant M. abscessus has emerged; the underlying resistance mechanism remains to be delineated fully. The present study confirmed the high rate of M. abscessus resistance to imipenem based upon analysis of a large number of clinical isolates obtained in mainland China.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, a small case series of paediatric patients with CF and M. abscessus demonstrated potential clinical utility of inhaled imipenem/cilastatin [136]. In a recent study in a mouse model of M. abscessus, inhaled tigecycline was highly efficacious and demonstrated intracellular activity within macrophages, an important finding given the limitations posed by intravenous tigecycline toxicity [137].…”
Section: Challengesmentioning
confidence: 97%
“…Recent studies have investigated the utility of inhaled antibiotics other than amikacin for treating MAB-PD. In a case series of two paediatric MAB-PD patients with poor response to various inhaled regimens, inhaled imipenem-cilastatin was well-tolerated and resulted in lung function stability [104]. In a granulocyte-macrophage colony-stimulating factor (GM-CSF) knockout mouse model of MAB infection, inhaled high-dose tigecycline was found to be effective in a dose-dependent manner at reducing pulmonary bacterial load and did not cause toxicity [105].…”
Section: Inhaled Agentsmentioning
confidence: 99%
“…Fragment-based screening approaches have been used to identify potential therapeutic target sites in M. abscessus [123]. In vitro inhibitors have Adding clofazimine to bedaquiline in vitro improves bacteriostatic effect of bedaquiline against M. abscessus (but promotes bedaquiline resistance); has modest effect on bactericidal effect of bedaquiline against M. avium (and slows emergence of bedaquiline resistance) [82] Tedizolid Concentration-dependent activity in vitro against M. avium; enhanced when combined with ethambutol Weak bacteriostatic activity in vitro against MAB; enhanced when combined with amikacin [85] Well-tolerated and efficacious in patient with pulmonary TB and liver transplant due to hepatic failure secondary to anti-TB medications [87] No significant difference in safety profile between tedizolid and linezolid when used to treat NTM infections in solid-organ transplant recipients [86] Probably contributed to anaemia in patient with pulmonary mycobacterial infection, and thrombocytopenia in patient with disseminated mycobacterial infection [88] Omadacycline Potent activity against rapid-growing NTM in vitro; similar activity to tigecycline against MAB, M. chelonae and M. fortuitum [89][90][91] Symptomatic improvement and radiographic stability at 1-month follow-up in a patient who had previously failed NTM-PD treatment following treatment with 4-week course of omadacycline plus amikacin and aztreonam [92] Tolerated for >7 months in a patient with MAB-PD; lobectomy required 5 months into omadacycline treatment [93] Associated with treatment success in five out of seven patients with MAB-PD; treatment failure in MAB-PD in one patient with fibrocavitary disease and one patient with nodular-bronchiectatic disease with dissemination [94] Eravacycline Inhaled imipenem-cilastatin well-tolerated and resulted in lung function stability in two paediatric MAB-PD patients [104] Inhaled high-dose tigecycline effective in a dose-dependent manner at reducing pulmonary bacterial load in a GM-CSF knockout model of MAB infection [105] Clofazimine inhalation suspension achieved four-fold higher concentration in the lungs than oral clofazimine and was well-tolerated in a mouse model of NTM lung disease [106] IFN-γ Inhaled IFN-γ improves NTM clearance in patients with IFN-γ deficiency [107] Inhaled IFN-γ poor at promoting sputum culture conversion among those with cavitary disease [108] Adjuvant intramuscular IFN-γ associated with higher treatment response rates relative to placebo and fewer disease-related deaths in MAC-PD [109] GM-CSF Adjuvant inhaled GM-CSF associated with improved lung function and culture conversion in two patients with CF and MAB-PD [112] Inhaled NO 160 ppm inhaled NO for 21 days fo...…”
Section: Inhaled Agentsmentioning
confidence: 99%